2009
DOI: 10.1097/aog.0b013e3181bd198c
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of the Cause of Endometrial Osseous Metaplasia

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Cayuela et al and Parente et al confirmed that the bony tissue was of maternal origin, thus representing true osseous metaplasia. 9,16 On the other hand, Tulandi et al found the bony tissue to be of fetal origin. 17 Differential diagnosis of this disorder include endometrial tuberculosis, IUCD, malignant mixed mullerian tumour of endometrium and retained fetal bones after abortion.…”
Section: Discussionmentioning
confidence: 99%
“…Cayuela et al and Parente et al confirmed that the bony tissue was of maternal origin, thus representing true osseous metaplasia. 9,16 On the other hand, Tulandi et al found the bony tissue to be of fetal origin. 17 Differential diagnosis of this disorder include endometrial tuberculosis, IUCD, malignant mixed mullerian tumour of endometrium and retained fetal bones after abortion.…”
Section: Discussionmentioning
confidence: 99%
“…Another study on genetic analysis of the cause of osseous metaplasia by Parente et al . also showed that DNA from the metaplastic tissue had the same origin as the patient .…”
Section: Discussionmentioning
confidence: 84%
“…However, some cases present either after very early abortion or without a history of pregnancy, suggesting a phenomenon of metaplasia of endometrial stromal cells into osteoblastic cells. This is supported by genetic sequencing which has identified identical DNA in bone fragments to that of the host, indicating that a host derivation is more likely than fetal tissue remnants 16 17. In addition, analysis of bovine endometrial stromal cells and equine placental mesenchymal stem cells has identified osteogenic properties, indicating a potential for osseous metaplasia 11 18.…”
Section: Discussionmentioning
confidence: 90%